Challenges facing black emerging farmers in transition from subsistance to commercial in Ba-Phalaborwa Municipality, Limpopo Province - Mathye, Dinny Diniwe (My University, 2017)
Despite the attempt by the South African government to transfer farms to black ownership, black farmers still remain poor and have to compete without technical skills. The majority of the previously disadvantaged farmers part of mostly practice subsistence agriculture characterised by low production and lack of market. The question that still remains to be answered is whether these subsistence farmers will ever grow to be commercial farmers, and white farmers continue dominating commercial farming. This prompted the researcher to engage in this study that will identify the challenges that make emerging farmers not to succeed as they should. The aim of this study is to investigate the challenges faced by black emerging farmers in the transition from subsistence to commercial farming in Ba-Phalaborwa Municipality and the role played by the Limpopo Department of Agriculture and Rural Development in ensuring that such transits take place. Data used in this study collected from 50 emerging farmers from the five villages in Ba-Phalaborwa and eight (8) extension officers from different sections in the department of Agriculture and Rural development in Ba-Phalaborwa Municipality. The researcher used mixed research design, questionnaires and semi-structured interviews to achieve the intended objectives. The finding shows that the majority of emerging farmers receive support to run their farm activities from the Department of Agriculture and Rural Development mostly in the form of extension services. The study further indicated that emerging farmers are aware of the role being played by the Department of Agriculture, and Rural Development although they are not satisfied with the support the Department is giving them and they believe that if the departments can further support them, they can improve their productions. The study established that emerging farmers have been facing several challenges, including lack of property right or title deed, insufficient farm size, shortage of money, inadequate extension services, inadequate or damaged infrastructure, and climate change, risk on production, lack of market, and lack of information, stock theft, erratic rainfall is a major challenge, lack of access to electricity, lack of access to telephone, not receiving advices on farming activities, not receiving advices on marketing of products, bookkeeping and technology. The emerging farmers’ challenges are worsened by the fact that farmers who are facing droughts are not able to get immediate funding to engage in farming activities. Despite these challenges emerging farmers want to continue with farming and in the next five years they want to see themselves in commercial farming. The concerned government departments should be encouraged to provide farm inputs and equipment like tractors, fertilisers, improved seeds, irrigation system and other types of farm inputs to emerging farmers to empower them to move from subsistence to commercial. The government departments and extension officers should be encouraged to provide skills to emerging farmers like, soil cultivation, irrigation, controlling of weed, packaging, livestock health care, hygiene, breeding and nutrition, recording skills and maintenance of farm equipment to empower emerging farmers to move from subsistence to commercial. Furthermore, policy makers should be encouraged to develop alternative strategies that will motivate emerging farmers to overcome challenges they are facing like lack of property rights of title deeds, insufficient farm sizes, climate change and shortage of money
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Government; Rural development; Agriculture; Farmers -- South Africa -- Limpopo; Agriculture; Subsistence farming -- South Africa -- Limpopo